Strengthening Religious Moderation Based on Local Wisdom in Building Islam-Christian Relations in Tangge Village, West Manggarai Regency - Siti Jelida (Tabéq: Journal of Local Wisdom, Belief, and Peace, 2025)
Religious Moderation Based on Local Wisdom in Building Islamic-Christian Relations. This type of research uses qualitative research; data collection is carried out through observation, interviews, and documentation. The research questions in this study consist of two questions, namely, 1) how are interfaith relations in the community of Tangge Village, West Manggarai Regency, and 2) how can religious moderation based on local wisdom be strengthened in building Islamic-Christian relations in Tangge Village, West Manggarai Regency. The objectives of this study are to analyse interfaith relations among the people of Tangge Village, West Manggarai Regency, and to identify and describe the strengthening of religious moderation, grounded in local wisdom, in building Islamic-Christian relations in Tangge Village, West Manggarai Regency. This research shows that Tangge Village demonstrates strong religious moderation practices, rooted in cultural and religious values, which are key to harmony between individuals and groups. Harmonious social relations, built through religious moderation, strengthen interfaith brotherhood. Religious moderation is a solution to dealing with extremist and fundamentalist groups. Its application in a multicultural society requires education as the primary basis and a socio-religious approach in religious and state life.